Effects of land use on soil COsub2/sub flux in the Paramo de Guerrero, Colombia (2016)
The Andean paramo is an important global carbon sink and has a fundamental ecological function of capture, regulation and supply of water resources. The soil CO2 efflux is a natural process through which the carbon is released into the atmosphere by molecular diffusion. The aim of this study was to establish the effect of different land use and soil managements practices over CO2 efflux in the Paramo de Guerrero, using the soil respiration chamber technique. We evaluated five different land covers present in the Paramo de Guerrero (paramo vegetation, pasture, two tillage cover and potato crop). Our results show that soil respiration was lower in the paramo (0.42 g CO2 m-2 h-1) than in the others land uses, probably due to the higher moisture content (57.1% on average). The tillage practices showed a primary physical effect, continued by the increase of the velocity of biological and chemical processes drived by soil microorganisms, such as microbial respiration and organic matter mineralization. This study demonstrates that moisture and soil temperature were not the main drivers of CO2 flux in the conditions of the Paramo de Guerrero, but the agricultural management and the land use affect differentially the accumulation and release dynamics of soil organic carbon to the atmosphere.